On the foundation of a general theory of stocks - Malte Faber; Karin Frank; Bernd Klauer; Reiner Manstetten; Johannes Schiller; Christian Wissel (University of Heidelberg, Department of Economics, 2003)
This essay develops the "concept of stocks" – a conceptual notion designed to enable a clearer understanding of the interaction between the dynamics of ecosystems and the economy. The notion of stocks is formulated in a general manner based on set theory. The central attribute of a stock is its temporal durability. Seen thus, stocks are suitable for depicting the influences a system's history has on its present – and hence for analysing temporal developments. Since permanency is a temporal attribute, the concept of stocks is not specifically limited to individual scientific disciplines and is suitable for interdisciplinary analysis. The notion is applied to economic and ecological examples and generalised for stochastic sets. The hierarchical structure of actual ecological-economic systems can be analysed by distinguishing the stock perspective from a system view. The theory of stocks is a building block for the conceptual foundations of ecological economics.
Keywords: A12; B40; Q20; 330; Dynamics; permanency; system; time scales; population; persistence; Umweltökonomik; Ressourcenökonomik; Theorie